2013
DOI: 10.1212/wnl.0b013e318282513b
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomeric dysfunction contributes to muscle weakness in facioscapulohumeral muscular dystrophy

Abstract: Objective: To investigate whether sarcomeric dysfunction contributes to muscle weakness in facioscapulohumeral muscular dystrophy (FSHD).Methods: Sarcomeric function was evaluated by contractile studies on demembranated single muscle fibers obtained from quadriceps muscle biopsies of 4 patients with FSHD and 4 healthy controls. The sarcomere length dependency of force was determined together with measurements of thin filament length using immunofluorescence confocal scanning laser microscopy. X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 12 publications
7
31
2
Order By: Relevance
“…In contrast, tension developed by pure type 1 fibers, which prevail in soleus muscle, is not reduced in transgenic mice, consistent with the minimal force reduction observed in this muscle. This is consistent with the report that muscle fibers isolated from FSHD patients produced a significant force reduction, specifically involving fast-twitch fibers (22). Moreover, our analysis reveals a fast-to-slow shift in fiber-type composition in some FRG1 transgenic muscles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, tension developed by pure type 1 fibers, which prevail in soleus muscle, is not reduced in transgenic mice, consistent with the minimal force reduction observed in this muscle. This is consistent with the report that muscle fibers isolated from FSHD patients produced a significant force reduction, specifically involving fast-twitch fibers (22). Moreover, our analysis reveals a fast-to-slow shift in fiber-type composition in some FRG1 transgenic muscles.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed the selective reduction of force in type 2 muscle fibers from FSHD patients (22). This similarity with our findings in FRG1 transgenics, led us to investigate whether TNNT3 splicing profile can be correlated with clinical features such as muscle weakness or histological features found in FSHD patients.…”
Section: R131 Altered Troponin T Splicing In Fshdsupporting
confidence: 88%
“…Since Type II fibers are the most commonly affected in Duchenne Muscular Dystrophy, it is thought that inducing the expression of Type I fibers will alleviate both the symptoms and progression of Duchenne Muscular Dystrophy. A similar trend was found in another type of muscular dystrophy, Facioscapulohumeral Muscular Dystrophy, as there is an early decrease in Type II fibers and an overall increase in the number of Type I fibers [29]. On the contrary, in myotonic dystrophy, Type I fibers are affected, as they atrophy more frequently and they lose a greater amount of force generation compared to Type II fibers [30][31][32].…”
Section: Muscular Dystrophiessupporting
confidence: 72%
“…A pilot study in 4 FSHD muscle biopsies performed in our laboratory supports this hypothesis [19]. The present study aims to confirm these data in a larger cohort and elucidate the causes of sarcomeric dysfunction in FSHD.…”
Section: Introductionsupporting
confidence: 62%